Menulis Ekspresif Untuk Mereduksi Kecemasan Korban Bullying - Dinda Ramadanti; Neni Noviza; Lena Marianti (Journal of Society Counseling, 2025)
The title of this research is “Expressive Writing to Reduce Anxiety Due to Bullying at Al-Kautsar Islamic Boarding School in Lahat.” The background of this research is that Islamic boarding schools have routines involving senior and junior students, which can make them vulnerable to bullying cases. Bullying is a form of child abuse where peers target someone who is perceived as weaker or lower in status to gain certain benefits or satisfaction. Bullying typically occurs repeatedly. For victims of bullying, this condition leads to physical and psychological pain, one of which is anxiety. The purpose of this study is to understand the anxiety experienced by bullying victims at Al-Kautsar Islamic Boarding School in Lahat and to examine the implementation of expressive writing therapy to address anxiety in bullying victims at the school. This study is field research with a qualitative approach and descriptive method. Data was collected through observation, interviews, and documentation. The subjects of the study were two female students from Al-Kautsar Islamic Boarding School in Lahat who experienced anxiety due to bullying. The analysis technique used was data collection, data reduction, presentation of data, and conclusion. The results showed that the anxiety experienced by bullying victims at the school included restlessness, physical tension, startled responses, rapid speech, lack of coordination, vulnerability to injury, social withdrawal, inhibition, avoidance of problems, hyperventilation, excessive vigilance, difficulty concentrating, tension, decreased creativity and productivity, confusion, feelings of guilt, fear of losing control, and recurring nightmares. The implementation of expressive writing therapy took place over four meetings, during which both subjects actively participated in the sessions and counseling until the end. The anxiety of both subjects decreased after the expressive writing activity, as evidenced by the scores they received post-activity. The conclusion of this study is that expressive writing can reduce anxiety in bullying victims at Al-Kautsar Islamic Boarding School in Lahat.